STRATEGI CITY BRANDING HUMAS PEMERINTAH KOTA BANDUNG SEBAGAI SMART CITY MELALUI PROGRAM SMART GOVERNANCE - Annisa Dwi P; Dini Salmiah FA (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
Increased globalization at the present time requires the municipality to compete against itsbranding including one of the city is the focus of Bandung smart city. Within three years the cityhas made to compete in the international arena to represent Indonesia was chosen as a 6thFinalist of the world for innovation Smart City of the World Smart City Organization inBarcelona. Public Relations of the Government of Bandung as a reflection of smart governancethat actively provide information and to interact actively with the audience through both onlineand offline media. Researchers used the constructivist paradigm with the aim of research to findout the city branding strategy undertaken by the Government Public Relations Bandung inrealizing smart city through smart governance program. This study uses descriptive qualitativemethod through interview data collection techniques. The object of this research is theGovernment Public Relations Bandung. Results of the study revealed that the strategy that isthrough the integration of online and offline communications through social media publishing,electronic and print, establishing media relations, and performed a special event.